2015
DOI: 10.1080/19476337.2015.1005027
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of biogenic amine concentration in fermented sausage by selected starter cultures

Abstract: View related articles View Crossmark data Citing articles: 5 View citing articles Reduction of biogenic amine concentration in fermented sausage by selected starter cultures Reducción de las proporciones de aminas biógenas en salchichas fermentadas mediante cultivos iniciadores seleccionados

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
(42 reference statements)
1
20
0
Order By: Relevance
“…As seen from results, there were significant differences in biogenic amines amounts of sucuk. In accordance with our study, previous researchers stated that the main biogenic amines in fermented sausages and sucuk were putrescine, cadaverine, histamine, tyramine and tryptamine (Gençcelep et al, 2007;Gençcelep et al, 2008;Kurt and Zorba, 2009;Lu et al, 2015;Xie et al, 2015). Putrescine was biogenic amine with the highest amount in sucuk samples whereas phenylethylamine and spermidine amounts in sucuk samples were found at low levels.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As seen from results, there were significant differences in biogenic amines amounts of sucuk. In accordance with our study, previous researchers stated that the main biogenic amines in fermented sausages and sucuk were putrescine, cadaverine, histamine, tyramine and tryptamine (Gençcelep et al, 2007;Gençcelep et al, 2008;Kurt and Zorba, 2009;Lu et al, 2015;Xie et al, 2015). Putrescine was biogenic amine with the highest amount in sucuk samples whereas phenylethylamine and spermidine amounts in sucuk samples were found at low levels.…”
Section: Discussionsupporting
confidence: 91%
“…The microorganisms from fermentation process may contribute to biogenic amines accumulation and their activities vary according to species and strain (Jairath et al, 2015;Kongkiattikajorn, 2015). The choice of suitable starter culture (amine negative starter culture) prevents the formation of high levels of biogenic amine in fermented sausages (Xie et al, 2015). Lactic acid bacteria are widely used in fermented sausages as starter or probiotic culture and inhibit undesired amine positive microorganisms to improve the quality and safety of final product because of their rapid acidification ability (Lu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, such procedures are considered inappropriate since it may disguise incidents of hygienic malpractice and/or spoilage [169]. The generally recommended and most efficient way of reducing and/or controlling BA formation in fermented sausages seems to be the use of nonaminogenic starter cultures [165,168,175,[178][179][180][181][182]. The use of a LAB starter culture results in a more rapid pH decrease than a spontaneous fermentation, thereby inhibiting contaminant Gram-negative bacteria and thus the potential for BA formation at the initial stages of the process.…”
Section: Biogenic Aminesmentioning
confidence: 99%
“…Zhang et al (Zhang, Lin, & Nie, 2013) found that adding an amine-negative Lactobacillus plantarum as starter culture can reduce the accumulation of PUT and CAD because of the rapid acidification and inhibition of undesirable bacteria, such as Pseudomonas and Enterobacteriaceae. Mangia et al (Mangia et al, 2013) and Xie et al (Xie et al, 2015) also found that BAs formation in sausage is reduced by adding L. plantarum.…”
Section: Introductionmentioning
confidence: 87%